Donor hepatitis C antibody positivity misclassifies kidney donor profile index in non‐hepatitis C‐infected donors: time to revise the kidney donor profile index – a retrospective cohort study. (5th October 2020) - Yazawa, Masahiko; Balaraman, Vasanthi; Tsujita, Makoto; Azhar, Ambreen; Talwar, Manish; Bhalla, Anshul; Potukuchi, Praveen K.; Eason, James D.; Kovesdy, Csaba P.; Molnar, Miklos Z.
Summary: The kidney donor profile index (KDPI) defines an hepatitis C (HCV) positive donor based on HCV antibody (Ab) and/or nucleic acid amplification test (NAT) positivity, with donors who are not actively infected (Ab+/NAT−) also classified as HCV positive. From Scientific Registry of Transplant Recipients dataset, we identified HCV‐negative recipients, who received a kidney transplant from HCV Ab+/NAT− ( n  = 116) and HCV Ab−/NAT− ( n  = 25 574) donor kidneys. We then compared recipients' estimated glomerular filtration rate (eGFR) at 6 months in matched cohorts, using combined exact matching (based on KDPI) and propensity score matching. We created two separate matched cohorts: for the first cohort, we used the allocation KDPI, while for the second cohort we used an optimal KDPI, where the HCV component of KDPI was considered negative in Ab+/NAT− patients. The mean ± SD age of the allocation KDPI‐matched cohort at baseline was 59 ± 10 years, 69% were male, 61% were white. Recipients' eGFR at 6 months after transplantation was significantly higher in the HCV Ab+/NAT− group compared to the HCV Ab−/NAT− group (61.1 ± 17.9 vs. 55.6 ± 18.8 ml/min/1.73 m 2, P  = 0.011) in the allocation KDPI‐matched cohort, while it was similar (61.8 ± 19.5 vs. 62.1 ± 20.1 ml/min/1.73 m 2, P  = 0.9) in the optimal KDPI‐matched cohort. Recipients who received HCV Ab positive, but NAT‐negative donor kidneys did not experience worse 6‐month eGFR than correctly matched HCV Ab−/NAT− recipients.